2020
DOI: 10.1101/2020.05.20.106666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arterial blood contrast (ABC) enabled by magnetization transfer (MT): a novel MRI technique for enhancing the measurement of brain activation changes

Abstract: AbstractFunctional brain imaging in humans is almost exclusively performed using blood oxygenation level dependent (BOLD) contrast. This typically requires a period of tens of milliseconds after excitation of the spin system to achieve maximum contrast, leading to inefficient use of acquisition time, reduced image quality, and inhomogeneous sensitivity throughout the cortex. We utilise magnetisation transfer to suppress the signal differentially from grey matter relative to blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…One possible explanation is that the macromolecules in the endothelial cells could give rise to an observable MT effect. Another explanation could be a mechanism of magnetization transfer studied in the context of functional MRI (Kim et al 2008, Pike et al 1992, Schulz et al 2020. In short, off-resonance MT-saturation pulses can efficiently saturate the water spins in cortical tissue, but not those in blood.…”
Section: Mtsat Associationsmentioning
confidence: 99%
“…One possible explanation is that the macromolecules in the endothelial cells could give rise to an observable MT effect. Another explanation could be a mechanism of magnetization transfer studied in the context of functional MRI (Kim et al 2008, Pike et al 1992, Schulz et al 2020. In short, off-resonance MT-saturation pulses can efficiently saturate the water spins in cortical tissue, but not those in blood.…”
Section: Mtsat Associationsmentioning
confidence: 99%
“…Intriguingly, we also show that the simple combination of saturation with a T 2 *‐weighted readout modulates the BOLD signal with minimal acquisition cost beyond a SAR increase and a slight SNR reduction. This adds an extra degree of freedom in fMRI signal optimization: the TE and tissue/venous suppression can be jointly optimized to, for example, increase contrast‐to‐noise and specificity in shorter TEs (Pfaffenrot & Koopmans, 2022 ; Schulz et al, 2020 ), thus increasing SNR and acquisition efficiency (a natural fit with spiral imaging; Kurban et al, 2022 ) or reduce the venous bias. In our current implementation and without the additional readout to negate BOLD contrast and thus isolate ABC, there is a sizable pial‐surface bias that renders the examination of cortical depth profiles challenging, similar to typical BOLD.…”
Section: Discussionmentioning
confidence: 99%
“…On‐resonance rectangular pulse‐trains with 0‐net flip‐angle can efficiently saturate a selected bandwidth of T 2 values in relation to the B 1 amplitude (Forster et al, 1995 ; Hu et al, 1992 ; van Gelderen et al, 2017 ). It was empirically found that at 95% SAR at 7 T, a pulse‐train consisting of seven phase‐modulated, nonslice‐selective, rectangular subpulses with B 1 = 10 μT (total duration = 6 ms; Priovoulos, Oliveira, et al, 2021 ; Schulz et al, 2020 ) could be repeated every 387 ms, thus allowing time for the readout of a 3D‐EPI segment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations